Pelatihan Kegawatdaruratan Berbasis Caring terhadap Kompetensi Profesional Perawat Emergency - Moch Masruri; Nursalam Nursalam; Kun Arifi Abbas; Daviq Ayatulloh; Diah Priyantini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the influence of caring-based emergency training on the professional competence of emergency nurses. The method used is quantitative with a quasi-experiment design (pre-post test with control group design). The research results showed that the caring-based emergency training given to the intervention group significantly influenced nurses' professional competence (p=0.000). The data testing results between groups after being given the intervention showed a significant change in the professional competence of nurses (p=0.000). In conclusion, caring-based emergency training effectively increases the professional competence of emergency nurses at RSUD Dr. Soetomo, Surabaya. An increase in nurse competency scores in both primary and secondary surveys demonstrates this. Keywords: Caring, Emergency, Professional Competency, Emergency Training, Nurse